Spatiotemporal regulation of cell fusion by JNK and JAK/STAT signaling during Drosophila wound healing. - Lee, J.H.; Lee, C.W.; Park, S.H.; Choe, K.M. (Journal of Cell Science, 2017)
Cell-cell fusion is widely observed during development and disease, and imposes a dramatic change on participating cells. Cell fusion should be tightly controlled, but the underlying mechanism is poorly understood. Here, we found that the JAK/STAT pathway suppressed cell fusion during wound healing in the Drosophila larval epidermis, restricting cell fusion to the vicinity of the wound. In the absence of JAK/STAT signaling, a large syncytium containing a 3-fold higher number of nuclei than observed in wild-type tissue formed in wounded epidermis. The JAK/STAT ligand-encoding genes upd2 and upd3 were transcriptionally induced by wounding, and were required for suppressing excess cell fusion. JNK (also known as Basket in flies) was activated in the wound vicinity and activity peaked at ?8?h after injury, whereas JAK/STAT signaling was activated in an adjoining concentric ring and activity peaked at a later stage. Cell fusion occurred primarily in the wound vicinity, where JAK/STAT activation was suppressed by fusion-inducing JNK signaling. JAK/STAT signaling was both necessary and sufficient for the induction of ?PS integrin (also known as Myospheroid) expression, suggesting that the suppression of cell fusion was mediated at least in part by integrin protein.